Marketing for Agrarian Reform Products Agroecological Rice from the Junco Lagoon (RS) - Betanho, Cristiane; Eid, Farid (Revista Gestão da Produção Operações e Sistemas, 2007)
The Landless Rural Workers Movement (MST) has tried to legitimize its actions in several ways. One is by offering settlement production to society. Thus, settled farmers organize themselves in cooperatives and associations seeking to produce and commercialize, without forgetting the ventures solidary nature. However, a large part of the production (generally raw materials and in natura products with low perceived added value) has been commercialized by middlemen or third parties, who add value, and consequently take possession of the additional values generated by this activity. This study, an excerpt from a doctoral thesis to be defended, shows a brief sketch of production and commercialization reality of a venture created and managed by settlers from the agrarian reform process, coordinated by the MST in Rio Grande do Sul. It aims to show the challenges of the process in understanding what value is to the client and add value to offers from a society perspective. From the results, an attempt is made to think of ways to strengthen this successful experience aimed at replicating it in other settlements in the state and Brazil while at the same time contributing with experiences for consolidating Solidary Economics as an alternative to improve income distribution in the country. Key words: Societal Marketing; Solidary Economics; Organic Foods; MST; Cooperatives.